Problems of legality strengthening in the sphere of motherhood protection - Suleymanov, Kh.; Abayev, M.; Saginbekov, K. (Bulletin of the Karaganda University “Law Series”, 2019)
Analyzing a current state of protection of motherhood in the Republic of Kazakhstan and having investigated the legislation of some foreign countries in the field of protection of motherhood, authors came to opinion on need of updating of the existing normative and legal acts regulating protection of motherhood. Besides, in the article problems of strengthening of legality in the sphere of protection of motherhood are considered. Ideas and suggestions for improvement of the legislation and law-enforcement practice in the sphere of providing the corresponding material benefits are expressed by authors, namely authors suggest to reconsider assignment of an award «Altyn alka» (Gold alka) and sequence of provision of housing for large families. In addition, the article deals with the problems of strengthening the rule of law in the field of maternity protection. The authors declare their ideas and proposals for improving the legislation and law enforcement practices in the field of ensuring mutually acceptable financial well-being. The legislation of the Republic of Kazakhstan of August 24, 2009, № 858 states that the process of adopting a law in the country is important for ensuring the guaranteed and unconditional fulfillment of the constitutional duties of all state and individuals, citizens and organizations.